Mental Capacity in the (Civil) Law: Capacity, Autonomy, and Vulnerability - Hall, Margaret (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2012)
This paper examines mental capacity as a medico-legal social construct and concludes that, while the construct works reasonably well in the contexts of property-related transactions and health-treatment decisions, it is deeply problematic and is a source of dysfunction in the context of guardianship and guardianship-type interventions. There is nothing natural, compelling, or necessary about the concept of mental capacity, and the author proposes an alternate construct more consistent with the purpose of guardianship and guardianship-type interventions: vulnerability. As the capacity construct is deeply enmeshed with a traditional liberal theory of autonomy (the capacity-autonomy equation or paradigm), so the vulnerability construct described here is more consistent with a theory of relational autonomy. The author contends that the conceptual framing provided by the capacity-autonomy paradigm in the guardianship context has precluded the coherent theorization of vulnerability, and she suggests a more coherent framework for doing so by drawing on theories of equity and relational autonomy.